Analysis of Vehicle Dynamics Motion on Performance Spring Under Vehicle Ride Condition - Yusman Zulhadi, Yusman Shahril Azam (Progress in Engineering Application and Technology, 2023)
Analysis of the dynamics of vehicle motion on various absorber parameters under ride conditions. The absorber parameters studied include a standard spring-damper system and a performance spring-damper system. The aim of this experiment to study sprung and unsprung behavior on various spring stiffness, to develop data acquisition system (DAQ) which can provide vehicle ride motion, and to analyze suspension performance testing during ride condition. The study was conducted using an Arduino Uno microcontroller as the processing unit and an accelerometer sensor as the input device. The output of the experiments was the acceleration measurements. The experiments were run in ride conditions, at speeds of 10 km/h, 15 km/h, and 20 km/h. The study used experimental approachs, the experimental setup consists of Arduino uno as the processor unit to measure the vertical acceleration of the vehicle. The vehicle dynamics data was collected and analyzed for both standard spring damper system and performance spring damper system. The data collected during the experiment was analyzed to determine the effect of different absorber parameters on the dynamics of the vehicle. The results of this study prove the unsprung acceleration from performance spring up to 2 g in the negative direction at 20km/h. The vertical acceleration of the vehicle with the performance spring is higher at the sprung mass, which has the potential to negatively impact the vehicle’s ride comfort which is the average improvement of vehicle with standard spring are -12.48% at 10 km/h, -11.17% at 15 km/h and -11.41% at 20 km/h. The results show that the standard spring-damper system can improve ride comfort and that the choice of absorber parameters can have a significant impact on the dynamics of a vehicle. Overall, this thesis contributes to the understanding of how absorber parameters affect the dynamics of a vehicle under standard road conditions and provide a new perspective on how absorber parameters can be optimized for improved ride comfort.